Project Based Learning in English for Specific Purposes (ESP) Course for Pre-Service Teacher - Indrasari, Nunun (Universitas Islam Negeri Raden Intan Lampung, 2016)
This paper attempts to explore the benefits and how Project Based Learning (PBL) is actually applied in ESP course. It also aims to investigate the problems arising in ESP course for pre-service teachers in English Education in IAIN Raden Intan Lampung. Teaching ESP course should cover both theoretically and practically. Pre-service teachers in IAIN Raden Intan Lampung tend to understand the theory but have no idea in applying it in real situation. PBL can be an alternative in teaching ESP course in which students are not only learning the theory but also making the project to implement the theory they have gotten. Besides presenting theories, the students of ESP course were asked to design course books for certain field of study. The books were designed based on the target need analysis that they have done by interviewing and observing the target situation. Assigning the book project enabled to raise the students’ creativity in designing an ESP course book both content focus and language focus. It can also stimulate the students’ ability in creating book design and template all at once. However, the lecturers’ guidance is necessary since some students are confused in determining and arranging exercises on the book.